Vocabulary Exposure to Islamic Institute Students Through an EFL Coursebook - Kirana, Dhinuk Puspita (IAIN Ponorogo, 2022)
The importance of vocabulary education in second and foreign language learning cannot be overstated. Teachers face a complex problem in teaching vocabulary because the English language contains hundreds of thousands of words, making it difficult to determine what to teach first. During their first semester at IAIN Ponorogo, students are exposed to English terminology by using a textbook required for English classes. The research aims to answer the following questions. They are 1) what are the coursebook's token types and sizes? (2) how many tokens, types, and word families are introduced in the coursebook? (3) what are the coursebook's vocabulary demands? (3) what vocabulary learning opportunities are offered in the coursebook? This study employed a corpus-based approach, and the analysis was carried out using RANGE, computer software. According to the findings, language learners who followed the coursebook were exposed to about 1,164-word families. Language learners need more vocabulary exposure from other sources to supplement the Nation's recommendation of focusing on the 2,000 most commonly used words.